2018
DOI: 10.1016/j.anorl.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Delayed endolymphatic hydrops. Special emphasis on nystagmus associated with episodes and contribution of chemical labyrinthectomy

Abstract: Nystagmus direction during vertigo episodes varies, and may initially present as vertical upbeating nystagmus, which, to our knowledge, has not been previously reported in DEH or Menière's disease. This nystagmus might reflect an inhibition of the superior semicircular canal (on the hearing-impaired side), suggesting incipient hydrops in this canal. Chemical labyrinthectomy is a simple and effective procedure in unilateral DEH, especially as the patient often suffers from total deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In MD, the nystagmus has classically been reported to be horizontal (13) beating either on the side or on the other side of the hearing loss, with up to three changes during a crisis (14)(15)(16)(17). The occurrence of a spontaneous vertical nystagmus in primary position of gaze is generally indicative of central nervous system pathology (18) but it has been recently documented during crisis of MD or DEH (19,20). This vertical nystagmus was either up or down beating (using a portable device) and later changed into a more classical horizontal-torsional component, beating controlaterally to the hearing loss (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In MD, the nystagmus has classically been reported to be horizontal (13) beating either on the side or on the other side of the hearing loss, with up to three changes during a crisis (14)(15)(16)(17). The occurrence of a spontaneous vertical nystagmus in primary position of gaze is generally indicative of central nervous system pathology (18) but it has been recently documented during crisis of MD or DEH (19,20). This vertical nystagmus was either up or down beating (using a portable device) and later changed into a more classical horizontal-torsional component, beating controlaterally to the hearing loss (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…37 Another study reported the usefulness of endolymphatic sac drainage operation in children with MD. 38 Endolymphatic surgery is aimed at draining, shunting, or decompressing the sac, thereby preventing hydrops by facilitating the outflow of endolymph. 39 This is considered a nondestructive surgical procedure.…”
Section: Treatmentmentioning
confidence: 99%
“…Initial upbeat nystagmus might reflect inhibition of the superior semicircular canal in the involved ear. 14 …”
Section: General Findingsmentioning
confidence: 99%